Nitrosyl ruthenium complexes with general formula [RuCl3,(NO)(P-P)] (P-P={PPh(2)(CH2)(n)PPh(2)},n=1-3 and {PPh(2)-CH=CH-PPh(2)}). X-ray structure of [RuCl3(NO){PPh(2)(CH2)(3)PPh(2)}] - Batista, A. A.; Pereira, C.; Queiroz, S. L.; deOliveira, LAA; Santos, RHD; Gambardella, MTD (Elsevier B.V., 1997)
Ruthenium(II) complexes with general formula [RuCl3(NO)(P-P)] were obtained in the solid state, where P-P = PPh(2)(CH2)(n)PPh(2) (n = 1-3) and PPh(2)-CH = CH-PPh(2). The P-31 NMR spectra of these compounds measured in CH2Cl2 showed only singlets, consistent with a fac configuration containing two equivalent phosphorus atoms, However the X-ray diffraction data show that the [RuCl3(NO){PPh(2)(CH2)(3)PPh(2)}] complex crystallizes in a met configuration, where one of the phosphorus atoms is trans to the NO group, in a slightly distorted octahedral geometry. Copyright (C) 1996 Elsevier B.V. Ltd
Keywords: ruthenium; nitrosyl; complexes; biphosphines; X-ray structure; isomerism